Vibrio cholerae-specific antibodies in plasma and saliva in cholera patients during a severe outbreak in Zambia: an antibody profiling approach - Luchen, Charlie C.; Ngo’mbe, Harriet; Liswaniso, Fraser; Bosomprah, Samuel; Zhiteneva, Julia A.; Harris, Jason; Charles, Richelle C.; Ryan, Edward T.; Sack, David; Bernshtein, Biana; Chisenga, Caroline C. (Frontiers in Immunology, 2025)
BackgroundCholera is a public health threat in resource-limited settings and is responsible for causing over 3 million cases globally. Mucosal immune responses play an important role in protecting against Vibrio cholerae infection, a non-invasive mucosal pathogen, yet traditional plasma-based assays are invasive and logistically challenging, particularly during outbreaks in low- and middle-income countries (LMICs). Saliva offers a unique window into mucosal immunity and may serve as a non-invasive alternative for seroprevalence and vaccine immunogenicity studies.MethodsWe conducted a cross-sectional antibody profiling study to analyse cholera-specific antibodies in saliva and plasma samples from 74 participants upon presenting to the cholera treatment centres. These were collected from four treatment centres in Lusaka during Zambia’s most severe cholera outbreak in 2024 caused by Vibrio cholerae O1 Ogawa. Levels of total IgG, IgG1-3, IgM, secretory IgA, and IgA1–2 isotypes were used to compare the biomarker profile between the two sample types.ResultsSaliva and plasma antibody profiles were comparable, with elevated IgA1 and IgA2 responses to cholera toxin-B (CtxB), sialidase, HlyA, and TcpA in saliva. Broader systemic responses were seen in plasma, including high CtxB-specific IgM, IgA1, and total IgG levels. Notably, biomarkers such as HlyA, Ogawa O-specific polysaccharide (OSP), and sialidase exhibited significant positive correlations between plasma and saliva. Elevated biomarker levels of HlyA, Ogawa O-specific polysaccharide (OSP), and sialidase in people living with HIV/AIDS (PLWHA) suggested immunological differences that warrant further exploration.ConclusionWe demonstrate that saliva is a viable, non-invasive alternative for cholera antibody-based profiling, offering practical advantages in resource-constrained settings. Given its strong correlation with systemic antibody profiles, saliva may be a practical sample for sero-surveillance in resource-limited settings. Future studies should investigate the duration of these salivary responses to further substantiate their use in estimating disease burden and immunity.